1997
DOI: 10.1080/10473289.1997.10464413
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Source Contributions to Ambient Aerosols in Central Taiwan

Abstract: Ambient aerosols were sampled at three selected sites in the coastal region of central Taiwan to obtain composition data for use in receptor modeling. All the samples were analyzed for 20 elements with an x-ray fluorescence spectrometer. The mass percentage of sulfates in particle samples was determined by ion chromatography, and mass percentages of elemental carbon (EC) and organic carbon (OC) were determined by an elemental analyzer. Because the three sampling sites were located within 25 km of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…An average mass loading of 85 to 250 μ g m −3 has been reported over the industrialized coastal regions along the west coast of India [ Khemani et al , 1994]. Similar investigations at coastal sites of Taiwan showed a seasonal average concentration of PM 10 in the range 37 to 93 μ g m −3 [ Chen et al , 1997; Tsai and Cheng , 1999; Chio et al , 2004] and a background PM 10 level of 23 μ g m −3 has been reported over the coastal sites in Spain [ Salvador et al , 2007]. These values are comparable to that observed at Trivandrum.…”
Section: Resultsmentioning
confidence: 84%
“…An average mass loading of 85 to 250 μ g m −3 has been reported over the industrialized coastal regions along the west coast of India [ Khemani et al , 1994]. Similar investigations at coastal sites of Taiwan showed a seasonal average concentration of PM 10 in the range 37 to 93 μ g m −3 [ Chen et al , 1997; Tsai and Cheng , 1999; Chio et al , 2004] and a background PM 10 level of 23 μ g m −3 has been reported over the coastal sites in Spain [ Salvador et al , 2007]. These values are comparable to that observed at Trivandrum.…”
Section: Resultsmentioning
confidence: 84%
“…For example, in urban areas in Taiwan, PM 2.5 was found to be as high as 80-90% of PM 10 , 302 and combustion was found to be a major source of both the coarse and fine PM. 303 Likewise, particles larger than 2.5 µm, or even larger than 0.5 µm, are rare in the central European urban environment. 304 The combination of particle size and chemical composition data provides insights into the sources.…”
Section: Source Apportionment and Modelingmentioning
confidence: 99%
“…As most time of 70 -90% is spend indoors, information on the indoor and outdoor relationships of PM concentrations is important. Indoor PM attributable to the outdoor air in urban/suburban residence houses has been the most serious indoor air pollution in Taiwan region [8][9][10][11][12][13][14]. In the indoor environment, the removal of entrained outdoor PM occurs through ventilation and deposition.…”
Section: Introductionmentioning
confidence: 99%